Simultaneous estimation of amoxicillin and dicloxacillin in bulk and capsule dosage form by chemometric assisted spectrophotometric methods - J. NEEHARIKA; P. SAI GEERVANI (International Journal of Pharma and Bio Sciences, 2018)
The objective/aim of the present study is to develop UV-Spectrophotometric method and to apply the chemometric designs to the developed method for the simultaneous estimation of Amoxicillin (AMX) and Dicloxacillin (DOX) in intact capsule dosage form without further extraction. The UV-Spectrophotometric method was developed by using 0.1N sodium hydroxide as solvent for both the drugs and the data generation from the absorption spectra was done by three chemometric designs which were based on the principles of Linear regression analysis method (LRC), Cramer’s matrix (CRM) and Method of least squares (MLS). The wavelength selected for all the above methods were 246 nm (wavelength of maximum absorption; λmax of AMX), and 219 nm (wavelength of maximum absorption; λmax of DOX). The developed methods were simple, economical and effective. These method need a separation techniques nor derivatization procedures.